Mood Moderates the Effect of Self-Generation During Learning - Schindler, Julia; Richter, Tobias; Eyßer, Carolin (Frontline Learning Research, 2017)
Generating information, compared to reading, improves learning and enhances long-term retention of the learned content. This so-called generation effect has been demonstrated repeatedly for recall and recognition of single words. However, before adopting generating as a learning strategy in educational contexts, conditions moderating the effect need to be identified. This study investigated the impact of positive and negative mood states on the generation effect with short expository texts. According to the dual-force framework (Fiedler, Nickel, Asbeck, & Pagel, 2003), positive mood should facilitate generation by enhancing creative knowledge-based top-down processing (assimilation). Negative mood, however, should facilitate learning in the read-condition by enhancing critical stimulus-driven bottom-up processing (accommodation). In contrast to our expectations, we found no general generation effect but an overall learning advantage of read compared to generated texts. However, a significant interaction of learning condition and mood indicates that learners in a better mood recall generated texts better than learners in a more negative mood, whereas no mood effect was found when the texts were read. The results of the present study partially support the predictions of the dual-force framework and are discussed in the context of recent theoretical approaches to the generation effect.